1978
DOI: 10.1128/iai.19.2.510-514.1978
|View full text |Cite
|
Sign up to set email alerts
|

Humoral bactericidal systems: antibacterial potential of serum from young animals

Abstract: The antibacterial potential of fresh serum obtained from young animals during a pre-antibody period of development was assessed against two smooth and two rough strains of gram-negative bacteria. The bactericidal capacity of serum from 3- to 4-week-old guinea pigs and 4- to 5-week-old rabbits was compared with that of serum from adults. Serum from young animals was deficient in natural antibodies, and in conventional dilution assays the bactericidal action was unimpressive, especially against the smooth strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…described in the present communication. may agree with the results of other investigators (19,24). Thus, it has been shown that fresh serum from young animals was efficient in killing gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…described in the present communication. may agree with the results of other investigators (19,24). Thus, it has been shown that fresh serum from young animals was efficient in killing gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it has been shown that fresh serum from young animals was efficient in killing gram-negative bacteria. including E. coli (24). This protective effect might have been induced by the gut flora ( 9 , 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an additional serum component, different from antibodies, must be required. This confirms the earlier observations of Skarnes, who investigated the antibacterial potential of serum from young rabbits and guinea pigs (8,11). The killing of the rough strains in the absence of "natural" antibodies required complement and at least one additional nonspecific component.…”
Section: Discussionsupporting
confidence: 90%
“…A second potential influence upon the neonatal resistance observed in this study would seem to be nursing, which in some animals acts as a vehicle for the transmission of resistance (6,8,59); colostrum and milk of several mammals are known to possess factors which may influence resistance (18,22,32,36,44,54). However, there has been no evidence to substantiate a role for similar factors outside the gastrointestinal tract of rabbits and this has led to the conclusion by several investigators that the systemic protective factors transmitted in utero to the rabbit fetus are not supplemented by nursing after birth (7,9,28,29).…”
Section: Discussionmentioning
confidence: 92%